Numerical and Optimization-Based Study on Split Hemispherical Shaped Fins for Augmenting Heat Transfer Rate - Ranjan, Alok; Das, Ranjan; Gajghate, Sameer S.; Barik, Debabrata; Majumder, Himadri; Cardoso, Elaine M. [UNESP]; Majumder, Arindam; Pal, Sagnik; Deb, Madhujit (Hindawi, 2023)
This paper deals with the numerical investigation of split hemispherical fins mounted staggered over a base plate. The thermal and flow analyses have been carried out to evaluate the Nusselt number (Nu), pressure drop ðΔPÞ, and hydrothermal performance factor (HTPF) with air as a medium and Reynolds number (Re = /3000 to 15000). The cylindrical fin (CF) and hemispherical fin (HF, of radius R) of the same volume and height have been formed and placed in the computational domain. Results reveal that the Nu for CF compared to HF is 1.3-1.4 times higher, with approximately 1.5 times higher ΔP for the given Re range. The value of HTPF for HF is greater than unity (/1.13-1.20) for all the considered Re values. Secondly, the HF gets split into longitudinal and transverse flow directions for better solid-fluid interaction. The geometrical parameters are transverse offset TO (/=0 − R/8), longitudinal offset LO (/=0 − R/8), and Re. Results show that the highest value of Nu (/=384.10) and HTPF (/=1.33) have been obtained at TO = R/10 (at LO =0) and TO = R/10 (at LO = R/10) for the highest Re (/=15000). At last, the cuckoo search algorithm (CSA) coupled with the response surface method (RSM) has been performed to fetch the optimum value of Nu based upon dimensionless TO∗, dimensionless LO∗, and Re. The optimum value (obtained at TO∗ =0:1, LO∗ =0, and Re = 15000) of Nu (=/392.16) from CSA is promising, with the numerically obtained Nu value (=/384.1059) with an error of 2.05%.